ADAPTIVE PHYSICAL TRAINING FOR CHILDREN WITH DIAGNOSIS OF CEREBRAL PALSY. - Aripova Vasila Baxtiyarovna (Research Focus International Scientific Journal, 2025)
The article examines the concept of adaptive physical education used for children diagnosed with cerebral palsy, draws attention to the fact that adaptive physical education is an effective means of motor rehabilitation for children. The methodology for conducting adaptive physical education classes with children with cerebral palsy is described in detail. A set of exercises for children with cerebral palsy is presented.